(untitled) (International Journal of Islamic Business, 2021)
Employee workplace commitment is one of an imperative topic nowadays in the organizational studies. Religion and money are among the several antecedents of employee commitment in organizations. Employees’ religion and organizational monetary reward practices are of eagerly importance in an employee career. Organizations have been facing lack of commitment in their workforce because of less consideration on the monetary as well as spiritual aspects. A comparative analysis between these two antecedents will be helpful to find out the true aspect behind this shortfall in the health sector. This study aims to investigate the relationship between monetary reward practices and religious affiliation with employee commitment. Data was collected from 233 Muslim employees of the health sector of Pakistan and the correlation and regression analysis were done by SPSS. The findings interpret that monetary reward practices were found to be highly related to employee commitment and having more effective influence as compared to employee’s religious affiliation. The current study suggests the health sector of Pakistan to take an account in providing monetary benefits to the employees to strengthen their workplace commitment.